TANTANAN BUDAYA MASYARAKAT DALU XB DUSUN IV KEC. TANJUNG MORAWA - Nurjannah; Bunga Nazlah; Dea Maharani; Khoirotun Nukmah Nasution; Nurul Aulia; Vivi Fatahsyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to examine the cultural challenges faced by the Dalu XB community in Hamlet IV, Tanjung Morawa District, in their daily social and cultural lives. Modern developments, globalization, and increasingly rapid social change have impacted the local cultural values ​​long held by the community. The research method used was a qualitative method with a descriptive approach, using observation, interviews, and documentation. The results indicate that the cultural challenges faced by the community include the ethnic origins of the majority of residents, their religious affiliation, the activities frequently carried out in the area, and the livelihoods of those living there. This research is expected to provide a deeper understanding of the cultural conditions of the Dalu XB community in Hamlet IV and provide consideration for relevant parties in efforts to preserve local culture amidst ongoing social change.